Factors Affecting the Dividend Payout Ratio in Pharmaceutical Companies - Natali Yustisia; Fitri Dwi Susanti; Ch. Endah Winarti (Management Research Studies Journal, 2023)
This research was conducted to examine the effect of current ratio, debt to equity ratio, and return on asset on dividend payout ratio. The types of data that used are secondary data from the annual reports of pharmaceutical companies listed on the Indonesian Stock Exchange period 2013-2021. The sample selection technique used purposive sampling and there are 6 (six) sample of pharmaceutical companies. Data analysis in this study used panel data regression with fixed effects as the selected model and processed using Eviews 10 software. The result of the research shows that the current ratio and debt to equity ratio have a positive significant effect to dividend payout ratio, but return on assets has no significant effect on dividend payout ratio. In addition, the current ratio, debt to equity ratio, and return on assets have a simultaneously effect on the dividend payout ratio. The adjusted R-Squared result was 0.418615 or 41.86 percent.